(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
It is generally accepted that levodopa drugs are the most effective means for the symptomatic treatment of Parkinson’s disease (PD). With a long course of PD during therapy with levodopa drugs, the clinical picture of the disease changes (clinical pathomorphosis occurs), levodopa induced dyskinesias and motor fluctuations occur [1]. Already 2 years after the start of taking dopa-containing drugs, the above complications occur in 50% of patients, and after 10 years - in 80–100%, they become an independent maladaptive factor affecting the daily activity of patients [2]. Levodopa-induced dyskinesias most often manifest in the lower extremities on the side of the body in which the symptoms of PD initially arose and in which the most pronounced manifestations of hypokinesia and rigidity are subsequently noted [3]. Dyskinesia significantly reduces the quality of life of patients, sharply limits their ability to work, and reduces their initiative; patients are forced to change their usual lifestyle. In many patients with PD, due to constant excessive motor activity, body weight decreases, disorders of the cardiovascular system may develop, and generalized hyperhidrosis occurs. In some cases, patients with switch-off dystonias develop a chronic pain syndrome, which may result in the development of affective disorder.